These hollow vows - Ryan, Lexi (Houghton Mifflin Harcourt, 2021)
Brie hates the Fae and refuses to have anything to do with them, even if that means starving on the street. But when her sister is sold to the sadistic king of the Unseelie court to pay a debt, she'll do whatever it takes to get her back--including making a deal with the king himself to steal three magical relics from the Seelie court. Gaining unfettered access to the Seelie court is easier said than done. Brie's only choice is to pose as a potential bride for Prince Ronan, and she soon finds herself falling for him. Unwilling to let her heart distract her, she accepts help from a band of Unseelie misfits with their own secret agenda. As Brie spends time with their mysterious leader, Finn, she struggles to resist his seductive charm. Caught between two dangerous courts, Brie must decide who to trust with her loyalty. And with her heart.